Effect of induced magnetic field on MHD mixed convection flow in vertical microchannel - Jha, Basant K.; Aina, Babatunde (Zielona Góra: Uniwersytet Zielonogórski)
The present work presents a theoretical investigation of an MHD mixed convection flow in a vertical microchannel formed by two electrically non-conducting infinite vertical parallel plates. The influence of an induced magnetic field arising due to motion of an electrically conducting fluid is taken into consideration. The governing equations of the motion are a set of simultaneous ordinary differential equations and their exact solutions in dimensionless form have been obtained for the velocity field, the induced magnetic field and the temperature field.
Keywords: microchannel; transverse magnetic field; induced magnetic field; velocity slip; temperature jump